Microvascular endothelial dysfunction is associated with albuminuria and CKD in older adults - Seliger, Stephen L.; Salimi, Shabnam; Pierre, Valerie; Giffuni, Jamie; Katzel, Leslie; Parsa, Afshin (BMC nephrology, 2016)
Background Impairment in glomerular endothelial function likely plays a major role in the development of albuminuria and CKD progression. Glomerular endothelial dysfunction may reflect systemic microvascular dysfunction, accounting in part for the greater cardiovascular risk in patients with albuminuria. Prior studies of vascular function in CKD have focused on conduit artery function or those with ESRD, and have not examined microvascular endothelial function with albuminuria. Methods We conducted a cross-sectional study among older hypertensive male veterans with stage 1–4 CKD, and hypertensive controls without CKD. Microvascular function was quantified by two distinct Laser-Doppler flowmetry (LDF) measures: peak responses to 1) post-occlusive reactive hyperemia (PORH) and 2) thermal hyperemia (TH), measured on forearm skin. Associations of each LDF measure with albuminuria, eGFR, and CKD status were estimated using correlation coefficients and multiple linear regression, accounting for potential confounders. Results Among 66 participants (mean age 69.2 years), 36 had CKD (mean eGFR 46.1 cc/min/1.73 m 2 ; 30.6 % with overt albuminuria). LDF responses to PORH and TH were 43 and 39 % significantly lower in multivariate analyses among those with macroalbuminuria compared to normoalbuminuria, (β= − 0.42, p = 0.009 and β= −0.37, p = 0.01, respectively). Those with CKD had a 23.9 % lower response to PORH compared to controls ( p = 0.02 after adjustment). In contrast, TH responses did not differ between those with and without CKD. Conclusions Microvascular endothelial function was strongly associated with greater albuminuria and CKD, independent of diabetes and blood pressure. These findings may explain in part the excess systemic cardiovascular risk associated with albuminuria and CKD.